PENGETAHUAN SISWA TENTANG SEKSUALITAS DENGAN PERILAKU SEKSUALITAS - Masamah Al M; Rabiah Marhabang; Novita Nindiana Wati (Poltekkes Kemenkes Surabaya, 2014)
One of the problems that occur as a result of juvenile delinquency are negative sexual behavior.Sexuality is holistic involving biopsychosocial aspects , cultural and spiritual teenagers. This research is akind of analytical research, the cross-sectional design, which aims to analyze the relationship of knowledgeabout sexuality with adolescent behavior adolescent sexuality in high school. The study population was thestudents of class X in a school, with a target population of 202 students, while the sample as many as 67students were taken with the Proportional random sampling technique . Independent variable is thestudents' knowledge about sexuality. Dependent variable is the Adolescent Sexuality Behavior . Resultscalculated p value = 2.72, then Hi is rejected so it can be concluded there is no association betweenknowledge about sexuality with adolescent sexuality behavior to students of class X in a school. It ishoped that the study site institution providing education about sexuality so much increased studentsknowledge about sexuality and sexual behavior impact and negative, so that the students can be moreaware and cautious of the current association . Keywords: Knowledge, Sexuality Behaviour